Pengaruh Lingkungan Kerja dan Motivasi Kerja terhadap Kepuasan Kerja Karyawan pada PT Telkom Indonesia Witel Bogor - Fanisa Mulia Rachmanda; Ade Sri Mulyani (Universitas Kristen Indonesia Toraja, 2024)
Human resources are the most important part in achieving success when achieving company goals. Success and failure that occur in achieving organizational goals depend on the capabilities of its human resources. This research aims to determine whether there is a partial and simultaneous influence of the work environment and work motivation on job satisfaction. This research uses a statistical quantitative approach and uses direct observation methods and questionnaire methods. This research was conducted in May - June 2024 at PT Telkom Indonesia Witel Bogor with a population of 49 respondents with a sample of 44. This research was tested by testing data quality, testing classical assumptions, testing hypotheses. From the results of the t test, the work environment has an insignificant influence on job satisfaction, and work motivation has a significant influence on job satisfaction. From the results of the f test, it was found that the calculated f was 139,242 > f table 3.23 and the sig was 0.000 < 0.05, so it was said that work environment variables and motivation had a simultaneous influence on job satisfaction.